Z-direction heat transfer in composites hybridised with large diameter metallic pins - Neale, Geoffrey; Fu, Y.; Skordos, Alexandros A. (ICCM - International Committee on Composite Materials, 2023)
Continuous fibre reinforced polymer composites have a well-established track record of excellent structural performance but generally lack non-structural functionalities inherent in legacy materials like metals. As the range of applications for composites continues to expand beyond their traditional base in aerospace, and to meet ambitious ‘Net Zero’ targets, there is increasing demand for embedded functionality in composites, like electrical or thermal energy transfer, though which a multitude of other functionalities are derived. A particularly under addressed challenge is how to efficiently achieve significant z-direction (through-thickness) functionality, which is restricted by the planar nature of composite. Through- thickness reinforcement (TTR) is typically used to achieve improvements in outof-plane structural performance but can be applied to the integration of hybridising elements, like metallics, that can impart desired functionality. Here we demonstrate that composite hybridisation by the addition of large diameter (2 mm) metallic pins positively affects the z-direction transfer of thermal energy through carbon-benzoxazine composite without adverse effects on in-plane mechanical performance. This work conducts extensive mechanical and thermomechanical characterisation of the carbon-benzoxazine composite and the metal-composite hybridised system which feeds into the development of an experimentally validated macroscale (ply-level) representative volume element (RVE) finite element (FE) model. The FE model captures both thermal energy transfer and thermomechanical behaviour of the hybridised system during operation. Results show that highly conductive pins significantly improve the local thermal conductivity and act to accelerate heat flow through the hybridised system, reducing thermal lag through-the-thickness.
Keywords: through-thickness reinforcement; hybridisation; multifunctionality; carbon fibre; benzoxazine